Performance evaluation of wireless smoke detector using RF module / Mohd Affendy Nani - Nani, Mohd Affendy (2011)
Nowadays, the new about building on fire does not quiet on the mass media, whether on newspapers, radio or television. It is very detrimental to our country with so many live were dying. So, to reduce these case, I would like to introduce this smoke sensor detector to every home. With this alarm detector, it can give us early warning about starting burning fire. With this alarm detector, we also have a time to saving our lives and some very important documents. So, it is very useful to us. This project presents the performance of wireless smoke sensor detector. The basic idea of the wireless sensor is to alert and early warning about starting burning fire. The hardware modules include the PIC microcontroller, smoke sensor, low battery, smoke sensor, RF module. The software component includes the program and code implemented via the PIC microcontroller. The smoke detector unit functions properly and in the manner it was originally planned and designed. There is a problem has occurred during the experimental session. The problem was interference from various external noise sources such as computers, phones, power sources and others since the smoke detector unit would beep alternately. However, this problem had no affect on the functionality of the smoke detector unit itself.